2022
DOI: 10.1038/s41598-022-09446-9
|View full text |Cite
|
Sign up to set email alerts
|

A community based cross sectional study on the prevalence of dyslipidemias and 10 years cardiovascular risk scores in adults in Asmara, Eritrea

Abstract: Despite the contribution of dyslipidemia to the high and rising burden of arteriosclerotic cardiovascular disease (CVD) in Sub-Saharan Africa; the condition is under-diagnosed, under-treated, and under-described. The objective of this study was to explore the prevalence of dyslipidemias, estimate a 10-year cardiovascular disease risk and associated factors in adults (≥ 35 to ≤ 85 years) living in Asmara, Eritrea. This population-based cross-sectional study was conducted among individuals without overt CVDs in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In our data, the incidence of EAC was disproportionately high in the Central Region, where Asmara, the capital city of Eritrea, is located. Interestingly, past reports have suggested that Asmara has a high incidence of obesity (high BMI and waist circumference) and metabolic syndrome [ 24 ]—the main risk factors for EAC [ 9 , 10 ]. By itself, this outcome highlights the possibility that EAC may become an increasingly important contributor to the future burden of EC in the country.…”
Section: Discussionmentioning
confidence: 99%
“…In our data, the incidence of EAC was disproportionately high in the Central Region, where Asmara, the capital city of Eritrea, is located. Interestingly, past reports have suggested that Asmara has a high incidence of obesity (high BMI and waist circumference) and metabolic syndrome [ 24 ]—the main risk factors for EAC [ 9 , 10 ]. By itself, this outcome highlights the possibility that EAC may become an increasingly important contributor to the future burden of EC in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Research suggests that a higher occurrence of dyslipidemia is often a marker of inadequate T2DM management and can worsen the onset of microvascular and macrovascular complications related to T2DM [8]. Surveys conducted in several African countries indicate that non-HDL-C predominates among lipid abnormalities [9,10]. However, research in the region suggests that LDL-C is the predominant factor [11].…”
Section: Introductionmentioning
confidence: 99%